2020
DOI: 10.3389/fmicb.2020.00581
|View full text |Cite
|
Sign up to set email alerts
|

The Potato Yam Phyllosphere Ectosymbiont Paraburkholderia sp. Msb3 Is a Potent Growth Promotor in Tomato

Abstract: The genus Paraburkholderia includes a variety of species with promising features for sustainable biotechnological solutions in agriculture through increasing crop productivity. Here, we present a novel Paraburkholderia isolate, a permanent and predominant member of the Dioscoreae bulbifera (yam family, Dioscoreaceae) phyllosphere, making up to 25% of the microbial community on leaf acumens. The 8.5 Mbp genome of isolate Msb3 encodes an unprecedented combination of features mediating a beneficial plant-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 91 publications
(105 reference statements)
4
33
0
Order By: Relevance
“…These gene clusters were highly similar to type III secretion systems in other beneficial bacteria, but distinct compared to phytopathogenic P. syringae . Also on the phyllosphere, type III secretion systems have been identified in the genome of a non-pathogenic Paraburkholderia isolate ( Herpell et al, 2020 ). However, more research is needed to determine the presence of type III secretion systems in other beneficial phyllosphere bacteria, to identify effectors associated with pathogens versus biocontrol effectors, and to determine the role of these type III secretion systems in beneficial host–microbe interactions.…”
Section: Indirect Interactionsmentioning
confidence: 99%
“…These gene clusters were highly similar to type III secretion systems in other beneficial bacteria, but distinct compared to phytopathogenic P. syringae . Also on the phyllosphere, type III secretion systems have been identified in the genome of a non-pathogenic Paraburkholderia isolate ( Herpell et al, 2020 ). However, more research is needed to determine the presence of type III secretion systems in other beneficial phyllosphere bacteria, to identify effectors associated with pathogens versus biocontrol effectors, and to determine the role of these type III secretion systems in beneficial host–microbe interactions.…”
Section: Indirect Interactionsmentioning
confidence: 99%
“…The present study was performed to formally classify strain Msb3 T , which was isolated from the phyllosphere of the 'air potato yam' , Dioscorea bulbifera [6]. Herpell et al [6] demonstrated that this strain is closely related to Paraburkholderia xenovorans and reported several genomic, taxonomic, functional and ecological characteristics of this organism.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Paraburkholderia contains species formally classified as Burkholderia that were separated from the latter on the basis of phylogenomic evidence [1]. The majority of Paraburkholderia species have been isolated from soil and plant roots or nodules but some have been found in aquatic environments and as opportunistic human pathogens, too [2][3][4][5][6][7]. Bacteria within the genus usually carry large genomes (7)(8)(9)(10) and are metabolically versatile.…”
Section: Introductionmentioning
confidence: 99%
“…The identified bacterial endophytes belong to the order Burkholderiales within the Betaproteobacteria (Yang and Hu, 2018). Certain forms of associations which might present early stages of the development of leaf nodule symbiosis or divergence from early forms of leaf nodule symbiosis, have also been reported (Lemaire et al, 2012;Herpell et al, 2020). Most endophytic bacteria have undergone evolutionary genome reduction as result of this symbiosis to an extend that they are no longer capable of freely living outside their host (Carlier and Eberl, 2012;Carlier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Candidatus Caballeronia crenata, the symbiont of A. crenata (Carlier et al, 2016) and a novel bacterial ectosymbiont Paraburkholderia sp. Msb3 from leaf acumens of Dioscorea bulbifera (Herpell et al, 2020). Considering the metabolic capabilities of both, plants and bacteria, there is evidence that leaf nodulated species might be a great resource for novel biologically active natural products.…”
Section: Introductionmentioning
confidence: 99%